Chemical contents and some trace metals of honeys produced in the Middle Anatolia region of Turkey - Turhan, Kadir (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2007)
A collection of 40 blossom honey samples from Middle Anatolia and surrounding areas in Turkey was sorted by botanical origin of the honeys. Compositional data measured in honeys were invert sugar, sucrose, 5-hydroxymethyl-2-furaldehyde (HMF), diastase number, free acid, lactone, pH, ash, proline and moisture. Average values were as follows: invert sugar 71.32%, sucrose 3.03%, HMF 4.52 mg/ kg, diastase number 16.27, free acid 16.61 meq/kg, lactone 5.65 meq/kg, pH 4.12, ash 0.25%, proline 47.44 mg/100 g, and moisture 16.39%. Quantitative analyses of 9 elements (Na, K, Ca, Fe, Cu, Mg, Zn, Mn and Co) in honey samples were performed using flame atomic absorption spectrometry (FAAS). The honeys were found to have ash contents lower than 0.6%, the limit set by Turkish Standards Institute (TSE).
Keywords: honey; HMF; invert sugar; trace metal; mineral content; BOTANICAL ORIGIN; MINERAL-CONTENT; PHYSICOCHEMICAL PROPERTIES; QUALITY EVALUATION; ELEMENTS; NA; CA; MG; CU; Environmental Sciences & Ecology